1998
DOI: 10.4049/jimmunol.160.9.4473
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 Regulates Liver Pathology in Acute MurineSchistosomiasis mansoniBut Is Not Required for Immune Down-Modulation of Chronic Disease

Abstract: We have used IL-10 gene knockout mice (IL-10T) to examine the role of endogenous IL-10 in the down-modulation of hepatic granuloma formation and lymphocyte responses that occurs in chronic infection with the helminth parasite Schistosoma mansoni. Although IL-10-deficient animals showed 20 to 30% mortality between 8 and 14 wk postinfection, they displayed no alterations in their susceptibility to infection and produced similar numbers of eggs as their wild-type littermates. The IL-10T mice displayed a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…tuberculosis growth [ 38 ]. In Schistosomiasis mansoni infection, a lack of IL-10 caused dysregulated Th1 responses, resulting in aggravated granulomatous inflammation and an increased mortality in the acute phase [ 39 ]. In C. trachomatis respiratory infection, IL-10 was reported to inhibit the priming and expansion of Th1 responses and contribute to the fibrotic reaction following infection [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…tuberculosis growth [ 38 ]. In Schistosomiasis mansoni infection, a lack of IL-10 caused dysregulated Th1 responses, resulting in aggravated granulomatous inflammation and an increased mortality in the acute phase [ 39 ]. In C. trachomatis respiratory infection, IL-10 was reported to inhibit the priming and expansion of Th1 responses and contribute to the fibrotic reaction following infection [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, treatment of schistosome-infected mice with exogenous IL-10 has been shown to directly regulate cellular responses and reduce immunopathological damage (39,40). Additionally, Wynn and colleagues (26) have demonstrated that in the absence of IL-10 (IL-10-deficient mice) there is an elevated type 1 cytokine profile with impaired granuloma formation and increased pathology during acute schistosome infection. In double IL-10-and IL-4-deficient or IL-10-and IL-12-deficient animals the central regulatory role for IL-10 in responses to schistosome eggs has been further delineated (41).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were restimulated with anti-CD3. IFN-␥ and IL-4 in cell supernatants were assayed as respective representative type 1 and type 2 cytokines; we also measured IL-10, as this cytokine has been shown to regulate type 1 responses during acute schistosome infection (25,26). CD3-stimulated cells from normal infected mice displayed IFN-␥ secretion and limited IL-4 secretion when examined 28 days after infection; later during infection this response was superseded by a type 2 dominated response, with reduced IFN-␥ production and marked enhanced secretion of IL-4 (Fig.…”
Section: Failure Of Egg-tolerized Mice To Down-modulate Type 1 Respon...mentioning
confidence: 99%